Effect of Mini-implant assisted Micro-osteoperforation on the rate of orthodontic tooth movement—A randomized clinical trial - Shresthaa Singh; Abhay K Jain; Raghu R Prasad; Anshu Sahu; Parul Priya; Priyanka Kumari (Journal of Orthodontic Science, 2023)
OBJECTIVE: To evaluate the effectiveness of micro-osteoperforation (MOP) over a 56-day period and to determine the influence of number of perforations on the rate of canine retraction. In addition, the amount of pain and discomfort caused by the MOP was evaluated. TRIAL DESIGN: A single-center, split-mouth, triple-blind, randomized, controlled trial. METHODS: 22 patients (18–30 years) who need fixed orthodontic treatment were recruited and randomly assigned to MOP1 and MOP2 groups. The recruited patients were divided into two groups with 1:1 allocation ratio. Randomization for the determination of experimental side and number of perforations was done using sealed envelopes. On each patient, the other side of mouth worked as control side with no MOPs. 4 months after first premolar extraction, patients in MOP1 received 3MOPs on the buccal surface of alveolar bone, whereas patients in MOP2 received three buccal and three palatal MOPs in the experimental side. The amount of canine retraction was measured every 28 days at two intervals on both sides of mouth. Pain perception was measured after 1 hr, 24 hr, 72 hr, 7 days, and 28 days of procedure. RESULTS: Result of the intra-examiner reliability using ICC is more than 0.97 (P < 0.001), indicating excellent repeatability and reliability of the measurements. The baseline characteristics between groups were similar (P > 0.05). A statistically significant difference in the rate of canine retraction on the MOP side was observed at the end of 56 days, amounting to two folds more than that of the control side. No significant difference was seen between MOP1 and MOP2 groups (P > 0.05). Mild-to-moderate pain was experienced only in first 72 hours of procedure. CONCLUSION: The study recommends that MOP procedure has substantial potential to be used as an adjunct to the routine mechanotherapy for accelerating tooth movement, as it may reduce treatment time by half in the first four weeks after the MOP procedure. TRIAL REGISTRATION: Clinical trial registry of India (CTRI/2022/12/048181).